Designing Pre-test Questions as Phone Notifications: Studying the Effects of a Mobile Learning Intervention - Herras, Ingrid Yvonne (Archīum Ateneo, 2019)
Mobile devices are increasingly becoming more pervasive and emerging as part of our daily life, particularly with university students. From these devices developed in tandem with face-to-face class interaction it has opened new possibilities for ubiquitous learning. We present out work on designing a smart-phone Mobile Learning application that streamlines pre-test questions into a “set it then forget it” input system where students can answer quiz items as slide-down notifications within the day prior to a scheduled lecture. Teachers using the application are afforded a web application to create pre-tests in advance and review class scores. The study was conducted to first-year Computer Science and Information Technology students of a university in the Philippines. Data collection techniques used in the study used experience questionnaires, usability tests, interviews, and tests of student learning outcomes. SUS testing showed consistent satisfactory scores across three iterations. Results from the Learning Experience questionnaire maps to the general answers from the focused group discussion presenting indicative of a positive learning experience. Evaluation of the pre and post test scores signified that using the mobile application can be an effective substitute to class administered tests.